Antioxidant stability study of sroegano essential oil microcapsules prepared by spray-drying - Asensio, Claudia Mariana (2017)
Release kinetics of the volatile compounds of oregano EO microcapsules and the relation with the antioxidant activity were studied. Different wall material (WM) to core (C) ratios (1:1 and 2:1; WM:C), addition of colloidal silicon dioxide (CSD); and different storage conditions: 23 °C (room temperature; R) and 4 °C (fridge temperature; F) were evaluated for 90 d. Volatile compounds, total phenolic content (TPC), free radical scavenging activity (FRSA), and Trolox equivalent antioxidant capacity (TEAC) were measured. The formulas 2:1 (WM:C) (R and F) without CSD behaved differently from the rest, exhibited a higher antioxidant activity, and released less amount of volatile compounds after 90 d. These treatments grouped together in the cluster analysis, showing the highest TPC (81.54 mg gallic ac/g), FRSA (8.66%), and TEAC (12.35 μg Trolox/g). The addition of CSD facilitated the released of volatile compounds through storage time and promoted losses in the antioxidant activity. The temperature had a significant effect in most of the evaluated variables. However, this effect was more noticeable in F2 (1:1, CSD). Practical Application: Oregano essential oil has antioxidant, antimicrobial, and sensory preserving properties. However, it is susceptible to volatilization and is degraded by external factors. Its addition into food matrices is restricted due to low solubility and hydrophobicity. The antioxidant activity of oregano EO is preserved after the process of microencapsulation by spray-drying that extends its stability during storage. Oregano EO microcapsules are an alternative of delivery which protects and extends the shelf life of this essential oil, overcomes stability related limitations and preserves its desirable characteristics allowing these kind of microcapsules to be later incorporated into food products. These microcapsules could be used as a natural additive/flavouring with antioxidant properties.